2007
DOI: 10.1007/s11060-007-9394-3
|View full text |Cite
|
Sign up to set email alerts
|

FOXG1 dysregulation is a frequent event in medulloblastoma

Abstract: Medulloblastomas represent 20% of malignant brain tumors of childhood. Although, they show multiple, non-random genomic alterations, no common, early genetic event involving all histologic types of medulloblastomas have been described. Nineteen medulloblastomas were analyzed using chromosomal comparative genomic hybridization (cCGH). Nine tumors with the most frequent number of genetic changes were further analyzed using bacterial artificial chromosome array CGH (aCGH). With aCGH, the frequency of gains and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 40 publications
2
43
0
1
Order By: Relevance
“…In this study, we showed that overexpression of FOXG1 in neuroblastoma cells reduces CDKN1A expression. This inhibitory role of FoxG1 on TGFβ-induced CDKN1A expression has already been described in earlier reports [Adesina et al 2007;Chan et al 2009]. The p.R244C FoxG1 mutant loses its effect, suggesting that this mutation affects the expression of CDKN1A at the transcriptional level in SH-SY5Y cells.…”
Section: Discussionsupporting
confidence: 78%
“…In this study, we showed that overexpression of FOXG1 in neuroblastoma cells reduces CDKN1A expression. This inhibitory role of FoxG1 on TGFβ-induced CDKN1A expression has already been described in earlier reports [Adesina et al 2007;Chan et al 2009]. The p.R244C FoxG1 mutant loses its effect, suggesting that this mutation affects the expression of CDKN1A at the transcriptional level in SH-SY5Y cells.…”
Section: Discussionsupporting
confidence: 78%
“…This promalignant function of NCAM1 is mediated by its interaction with fibroblast growth factor receptor (38,48). FOXG1 acts as an oncoprotein inhibiting TGF-b-mediated antiproliferative responses in medulloblastomas and ovarian cancer cells through suppressing p21 WAF1/CIP1 transcription (37,49). Integrins are the most important matrix receptors and their downregulation can promote dissemination of primary tumor but also suppress the attachment of already migrating tumor cells at distant sites.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, neither beneficial effects of these manipulations require irreversible transgene activation (Figs. 5, 7), especially biohazardous in the case of Foxg1 [68,69], nor do these manipulations induce any transformation foci (data not shown), so making them even more appealing for therapeutic approaches. Hopefully, delivering these treatments by molecular tools different from lentivectors, besides preventing genotoxicity of multiple insertional mutations [70], will fully unveil the neuronogenic potential of such manipulations (Figs.…”
Section: Potential Therapeutic Implicationsmentioning
confidence: 99%